2022
DOI: 10.1111/jvh.13761
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus‐specific immune responses following direct‐acting antivirals administered during recent hepatitis C virus infection

Abstract: Individuals who spontaneously clear hepatitis C virus (HCV) infection have demonstrated evidence of partial protective immunity, whereas treatment-induced clearance provides little or no protection against reinfection. We aimed to investigate whether treatment of acute HCV infection with direct-acting antivirals (DAA) prevents establishment of, or reverses, T-cell exhaustion, leading to a virus-specific T-cell immune profile more similar to that seen in spontaneous clearance. The magnitude and breadth of HCV-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…However, one study found that only a partial restoration of immune responses could be obtained in HCV patients treated with DAAs, with increased proliferation of HCV-specific CD4 and CD8 T cells, accompanied by an impaired ability to secrete IFNγ and IL2 [ 101 ]. Also, a recent study highlighted the importance of early DAA treatment commencement during the acute phase of HCV infection, which led to a reduction in immune exhaustion and to stronger HCV-specific T cell responses after treatment, thus reducing the risk of possible reinfection [ 102 ].…”
Section: Can Direct-acting Antivirals (Daas) Reverse Hcv-altered Immu...mentioning
confidence: 99%
“…However, one study found that only a partial restoration of immune responses could be obtained in HCV patients treated with DAAs, with increased proliferation of HCV-specific CD4 and CD8 T cells, accompanied by an impaired ability to secrete IFNγ and IL2 [ 101 ]. Also, a recent study highlighted the importance of early DAA treatment commencement during the acute phase of HCV infection, which led to a reduction in immune exhaustion and to stronger HCV-specific T cell responses after treatment, thus reducing the risk of possible reinfection [ 102 ].…”
Section: Can Direct-acting Antivirals (Daas) Reverse Hcv-altered Immu...mentioning
confidence: 99%